Anatomy and phylogenetic relationships of a new catfish species from northeastern Argentina with comments on the phylogenetic relationships of the genus Rhamdella Eigenmann and Eigenmann 1888 (Siluriformes, Heptapteridae) - Bockmann, Flávio (2008)
Rhamdella cainguae, a new species of the family Heptapteridae is described from the Arroyo Cuña-Pirú, a tributary of the Río Paraná, in the subtropical forest of Misiones, northeastern Argentina. The presence of a large differentiated ovoid area on the supraorbital laterosensory canal along the frontal-sphenotic boundary, delimited by the slender dorsal walls of the bones, and with no foramen for a laterosensory branch, is an autapomorphy for R. cainguae. A detailed description of the skeleton and laterosensory system of R. cainguae is provided. The genus Rhamdella is rediagnosed on the basis of three autapomorphies: a very large opening in the frontal for the exit of the s6 (epiphyseal) branch of the supraorbital laterosensory canal (reversed in R. rusbyi), a large optic foramen, and a dark stripe along the lateral surface of the body (reversed in R. rusbyi). Rhamdella is considered to be the sister group of a large heptapterid clade composed of the Nemuroglanis sub-clade plus the genera Brachyglanis, Gladioglanis, Leptorhamdia, and Myoglanis. Rhamdella is herein restricted to five valid species: R. aymarae, R. cainguae, R. eriarcha, R. longiuscula, and R. rusbyi. A sister group relationship between R. aymarae and R. rusbyi is supported by three synapomorphies. Rhamdella cainguae shares 12 apomorphic features with R. eriarcha and R. longiuscula.